From acute food insecurity to famine: how the 2023/2024 war on Gaza has dramatically set back sustainable development goal 2 to end hunger - Hassoun, Abdo; Al-Muhannadi, Khawla; Hassan, Hussein F.; Hamad, Ahmed; Khwaldia, Khaoula; Buheji, Mohamed; Al Jawaldeh, Ayoub (Frontiers in Sustainable Food Systems, 2024)
The widespread destruction and the devastating humanitarian toll caused by the ongoing war on Gaza have transformed this besieged Strip into a place of death and despair. This review will explore the implications of this war for food security, focusing on Sustainable Development Goal (SDG) 2, which seeks to fight malnutrition and food insecurity and achieve zero hunger by 2030. This work is based on a review of grey literature, such as reports from government and non-governmental agencies, as well as recent scientific journal publications. Our results show that the ongoing war on Gaza has exacerbated the already acute food insecurity that Gazans have been struggling with since the blockade was imposed in 2007. Restless bombardment and ground operations have damaged or even razed agricultural land and all food production infrastructure (such as bakeries, mills, and food processing facilities), destroying Gaza’s food system. Facing catastrophic levels of hunger, some families, especially in northern Gaza have recently been resorting to eating animal feed and weeds to survive. With the starvation of civilians being used as a method of warfare, many experts and human rights organizations argue that Gaza is now the world’s worst hunger crisis and its population is on the verge of famine, if not already there. Moreover, this unprecedented humanitarian crisis in Gaza could have significant consequences on global food security in its six pillars, jeopardizing the implementation of SDG 2. While international organizations are making efforts to mitigate the catastrophic food shortage and famine, more comprehensive and sustainable solutions are needed to address the root causes of food insecurity in Gaza and ensure that all residents have access to an adequate and nutritious diet.